TLR9 gene polymorphism -1237T/C (rs5743836) is associated with low IgG antibody response against PvCSP variants in symptomatic P. vivax infections in Venezuela. - Fhabián S Carrión-Nessi; Eva Salazar-Alcalá; David A Forero-Peña; Kellys A Curiel; Mary Lopez-Perez; Mercedes Fernández-Mestre (PLoS Neglected Tropical Diseases, 2025)
Background Clinical immunity to malaria has been associated with humoral immune responses targeting asexual-stage parasite proteins. However, the variability in antibody-driven responses may be influenced by genetic factors in the human host. This study aimed to evaluate the frequency of SNPs in the TLR9 gene and their association with IgG antibody responses against PvCSP variants (VK247, VK210, and V-like) and PvMSP-119 among individuals presenting with symptomatic Plasmodium vivax infections in a malaria-endemic region of Venezuela. Methodology/principal findings A cross-sectional study was conducted in Bolívar state, Venezuela, involving 210 individuals infected with P. vivax. IgG reactivity against P. vivax recombinant antigens was assessed by ELISA, and three TLR9 gene SNPs (rs5743836, rs352140, and rs187084) were genotyped by PCR. The median age of individuals was 29 years, with the majority being male miners with a prior history of malaria. Over 90% of individuals exhibited IgG antibodies against the three PvCSP variants and PvMSP-119. High responders to the PvCSP variants reported fewer symptoms compared to medium (p < 0.001) and low (p < 0.001) responders. Among the analyzed SNPs, heterozygous genotypes were the most prevalent. Using an overdominant inheritance model, carrying the heterozygous genotype (T/C) for TLR9 gene SNP rs5743836 was associated with lower IgG antibody response against PvCSP VK247 (aOR = 0.26, 95% CI = 0.09 to 0.73, p = 0.0094) and PvCSP V-like (aOR = 0.37, 95% CI = 0.14 to 0.99, p = 0.047). No significant associations between inheritance models for the three SNPs and parasitemia were observed. Conclusions/significance These findings suggest that TLR9 gene variability, particularly the heterozygous genotype for SNP rs5743836, may influence the IgG antibody response against PvCSP VK247 and V-like. Identifying genetic traits that impact immune response development could be valuable for malaria vaccine design and implementation.